(untitled) (Journal of the College of Education for Women, 2019)
The consequences of divorce after separation have several legal and legal provisions among them is that the wife must wait for a certain period specified by the legislator before marrying another, whether her husband left her after the practice of interning or died until the expiration of the period of counting and compensation for arbitrary divorce and the right of the unmarried to live in the marital home and complete her dowry is gold. But it cannot block the object of material and moral damage, especially if it was fired without shortening them and therefore these rights were decided by the provisions of the absolute and remove the effects on its reputation